1999
DOI: 10.1073/pnas.96.8.4610
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli genes regulated by cell-to-cell signaling

Abstract: Utilizing the bicistronic reporter transposon mini-Tn5 lacZ-tet͞1, we have identified lacZ fusions to four Escherichia coli genes͞operons that are strongly activated by the accumulation of self-produced extracellular signals. These fusions were designated cma9, cma48, cma113, and cma114 for conditioned medium activated. Each of the cma fusions was expressed in a growth phase-dependent manner, and the presence of conditioned medium from a stationary phase E. coli culture resulted in the premature activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 39 publications
0
95
0
1
Order By: Relevance
“…Thus, the induction of E. coli drug exporter genes by indole is not likely to be a result of the envelope stress response. Recently, it was reported that indole acts as an extracellular signal like N-acyl homoserine lactone and AI-2 (Baca- DeLancey et al, 1999;Fuqua et al, 2001;Wang et al, 2001;Bassler, 2002;Chen et al, 2002). The indole concentration increases with cell growth as a byproduct of pyruvate production in E. coli cells (Wang et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the induction of E. coli drug exporter genes by indole is not likely to be a result of the envelope stress response. Recently, it was reported that indole acts as an extracellular signal like N-acyl homoserine lactone and AI-2 (Baca- DeLancey et al, 1999;Fuqua et al, 2001;Wang et al, 2001;Bassler, 2002;Chen et al, 2002). The indole concentration increases with cell growth as a byproduct of pyruvate production in E. coli cells (Wang et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Indole is generated through the degradation of tryptophan by tryptophanase, the product of the tnaA gene, and can reach levels up to 340 mM in stationary-phase cultures of E. coli. The role of indole as a potential signal molecule in E. coli was first revealed through analysis of factors required for the induction of the astD, tnaB and gabT genes by E. coli conditioned medium (Baca-DeLancey et al, 1999;Wang et al, 2001). Although indole itself acted as an inducer, conditioned medium from a tnaA mutant was still able to induce these genes, albeit to a lower extent than the wild-type.…”
Section: Indolementioning
confidence: 99%
“…Bacillus subtilis has become the best studied grampositive model organism for a number of reasons which includes its relative ease of handling in wet lab experiments, its growth rate is relatively fast (comparable to that of Escherichia coli), it possesses a natural competence system and the machinery for homologous recombination (Baca-DeLancey et al 1999). In Gram positive bacteria signal molecule is a post-translationally processed secreted peptide for the communication.…”
Section: Introductionmentioning
confidence: 99%